Dates of publication of the Zoology parts of the Report of the Scientific Results of the Voyage of H.M.S. Challenger During the Years 1873–76 - Low, Martyn E. Y.; Evenhuis, Neal L. (Zootaxa, 2013)
The dates of publication and exact titles of the 83 parts of the Zoology of the Report of the Scientific Results of the Voyage of H.M.S. Challenger During the Years 1873–76 are presented. Exact dates of publication for 71 of these parts have been determined using notices of their publication in contemporary publications. The dates of publication of the two Narrative volumes of the voyage of the H.M.S. Challenger (which contain available indications of new names) are also determined.